2014
DOI: 10.1007/s11606-014-3100-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Referral Communication Between VHA Primary Care and Specialty Care

Abstract: BACKGROUND:Poor communication between primary care providers (PCPs) and specialists is a significant problem and a detriment to effective care coordination. Inconsistency in the quality of primary-specialty communication persists even in environments with integrated delivery systems and electronic medical records (EMRs), such as the Veterans Health Administration (VHA). OBJECTIVE: The purpose of this study was to measure ease of communication and to characterize communication challenges perceived by PCPs and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 29 publications
6
86
0
Order By: Relevance
“…In an earlier study, Poon et al [27] found that primary care physicians reviewed 1000 individual diagnostic studies weekly and spent an average of 74 min per day doing results reviews. Technology, such as electronic medical records (EMRs) is a strategy for information and knowledge management [10]. Technology, however, has its own challenges and workload demands [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier study, Poon et al [27] found that primary care physicians reviewed 1000 individual diagnostic studies weekly and spent an average of 74 min per day doing results reviews. Technology, such as electronic medical records (EMRs) is a strategy for information and knowledge management [10]. Technology, however, has its own challenges and workload demands [28].…”
Section: Discussionmentioning
confidence: 99%
“…One recent mixed methods study within the Veteran Hospital Administration (VHA) found that a shared EMR was no panacea for an effective referral process. Effective referral communications were influenced by opportunities for primary care-specialist physicians to engage in other forms of dialogue and more personal interactions (e.g., telephone, face-to-face) that promoted collaborative relationships and trust among physicians [10]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These messages would often be of a friendly nature including phrases such as "dear Dr" or "kind regards". This highlights the fact that a consultation is not merely an exchange of information but also a collaboration that requires personal communication [60].…”
Section: Usefulness Of Contentmentioning
confidence: 99%
“…In interviews, primary care physicians have praised the potential of e-Consults as a fast and easy way to increase efficiency of provider communication (Zuchowski et al, 2015). Early survey results show very high rates of satisfaction among primary care physicians (93 percent satisfied) and patients, with lower satisfaction rates for specialists (53 per cent satisfied).…”
Section: A New Form Of Telehealth: E-consultsmentioning
confidence: 99%